Immersive Virtual Reality: A Safe, Scalable, Non-opioid Analgesic for Military and Veteran Patients - Peterson, Barry N.; Hitching, Rita; Howard, Lisa; Zhu, Kaitlly; Fontenot, Miles R.; Alhalabi, Wadee; Seibel, Asher; Harris, Odette A.; Madrigal, Esmeralda; Adamson, Maheen Mausoof; Hoffman, Hunter G. (Frontiers in Virtual Reality, 2021)
In Iraq and Afghanistan over 75% of the combat casualties suffered by U.S. troops have involved explosive devices. Improvements in body armor and advances in military medicine have significantly reduced the number of combat-related fatalities, but have greatly increased the number of U.S. active component personnel suffering painful trauma injuries. Unfortunately, so far, advances in pharmacologic analgesia pain medications have not kept pace with advances in survivability. For many active component personnel and Veterans, pain is a top health complaint from patients. The opioid epidemic has increased the urgency of developing powerful non-pharmacologic approaches for the management of pain. Immersive VR is proving to be a powerful non-opioid pain management technique for acute pain. However, the cost and usability limitations of pre-2016 VR clinical products resulted in limited treatment adoption rates for clinical use. In recent years, VR technology has become increasingly immersive, portable, and miniaturized, requiring minimal technical expertise to operate, and low-cost, factors that are likely contributing to the recent increase in the clinical use of VR analgesia. VR is greatly benefitting from a growing string of major technological breakthroughs and VR treatment improvements that will likely continue to increase the effectiveness and suitability of VR analgesia for military and VA patients. Regarding acute pain, we propose that the next revision to the current Tactical Combat Casualty Care guidelines consider including VR as an effective and hemodynamically safe approach to the current management of acute trauma pain in military personnel during medical procedures. With recent miniaturization and ruggedization, VR can potentially be used closer to the battlefield in the future. Beyond distraction, innovative VR therapy techniques designed to help reduce chronic pain are discussed. Recent breakthroughs in the mass production of inexpensive, highly immersive lightweight stand alone VR systems and augmented reality systems increase the potential for widespread dissemination of VR analgesia for acute and potentially for chronic pain. For example, the U.S. military recently purchased 22 billion dollar’s worth of Microsoft Hololens mixed reality systems (e.g., for training). Expanded research and development of VR analgesia customized for the unique needs of military and VA patients is recommended.